2003
DOI: 10.1196/annals.1288.020
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Diabetes in Swedish Bank Voles (Clethrionomys glareolus): Signs of Disease in Both Colonized and Wild Cyclic Populations at Peak Density

Abstract: Colonized bank voles (Clethrionomys glareolus) originating from Sweden developed type 1 diabetes. Animals became polydipsic, glucosuric, and hyperglycemic and gradually developed a lethal ketoacidosis. Pancreas in animals with end-stage disease showed total destruction of islet cells. Interestingly, also a high proportion of wild bank voles in cyclic populations that were trapped at (or close to) the cyclic population density peak frequently showed high blood glucose levels and pathological glucose tolerance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
49
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 9 publications
1
49
0
Order By: Relevance
“…This pathogen, subsequently named the Ljungan virus (LV), has been identified in wild voles in Denmark and the United States, as well as in lemmings and inbred laboratory rats (Johansson et al, 2003;Niklasson et al, 2003aNiklasson et al, , 2006aNiklasson et al, , 2007aSamsioe et al, 2006). In addition, LV has been shown to induce type 2-like diabetes, uterine resorptions, malformations, and neonatal death in CD-1 laboratory house mice (Niklasson et al, 2006b;Samsioe et al, 2006).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This pathogen, subsequently named the Ljungan virus (LV), has been identified in wild voles in Denmark and the United States, as well as in lemmings and inbred laboratory rats (Johansson et al, 2003;Niklasson et al, 2003aNiklasson et al, , 2006aNiklasson et al, , 2007aSamsioe et al, 2006). In addition, LV has been shown to induce type 2-like diabetes, uterine resorptions, malformations, and neonatal death in CD-1 laboratory house mice (Niklasson et al, 2006b;Samsioe et al, 2006).…”
mentioning
confidence: 99%
“…In 1998, Niklasson and colleagues isolated a picornavirus in natural populations of the bank vole (Myodes glareolus) in northern Sweden that causes clinically recognizable type 1 diabetes-like symptoms in this species (Niklasson et al, 1998(Niklasson et al, , 1999(Niklasson et al, , 2003a. This pathogen, subsequently named the Ljungan virus (LV), has been identified in wild voles in Denmark and the United States, as well as in lemmings and inbred laboratory rats (Johansson et al, 2003;Niklasson et al, 2003aNiklasson et al, , 2006aNiklasson et al, , 2007aSamsioe et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This led us to hypothesise that the bank vole is the reservoir and/ or vector of an infectious agent causing this disease in a predisposed population of humans. The hypothesis was supported by the observation that wild-trapped bank voles developed symptoms of diabetes in captivity [2]. A novel picornavirus, Ljungan virus (LV), has been isolated from diabetic bank voles in Sweden.…”
mentioning
confidence: 94%
“…A novel picornavirus, Ljungan virus (LV), has been isolated from diabetic bank voles in Sweden. Furthermore, viral antigen and picorna viral-like particles were detected by immunohistochemistry (IHC) and electron microscopy in affected pancreatic beta cells [2,3]. Analysis of new and stored samples have shown that LV is also present in wild voles in Denmark and the USA [4].…”
mentioning
confidence: 99%